High-erosion-resistant steel cord and process for manufacturing same
Patent Information
- Application Number
- CN202510867519.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-06-26
AI Technical Summary
[0004]本发明的目的在于针对传统钢丝帘线黄铜镀层在潮湿环境中耐蚀性不足、易剥落的缺陷,提供一种强化钢丝基体与镀层自身耐蚀性能的高抗蚀性钢丝帘线及其制备工艺
本发明的帘线相比于传统钢丝帘线强化了钢丝基体与镀层自身的抗蚀性能,通过帘线钢丝基体表面、镀层、镀层表面处理由内至外的三相协同作用共同加强对帘线自身的防护,使得钢丝帘线对环境腐蚀介质的抵抗能力大幅增强,特别是对湿热腐蚀介质,且不会恶化其与橡胶的结合能力。
Smart Images

Figure CN120592049B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high corrosion-resistant steel wire cord and its preparation process, belonging to the field of steel wire product manufacturing. Background Technology
[0002] As a key reinforcing skeleton in rubber composites, steel cord is exposed to complex conditions such as humidity, heat, salt spray, dynamic stress, and chemical media for extended periods. Its corrosion resistance directly determines the material's service life and safety. Coating is a crucial process in steel cord production, aiming to improve corrosion resistance, optimize adhesion to the rubber matrix, and reduce frictional losses during processing. Traditional steel cord coatings primarily use brass plating, which has long been the mainstream surface treatment technology due to its electrical conductivity and chemical bonding ability with rubber vulcanization. However, traditional brass plating still faces significant technical bottlenecks in practical applications. Brass plating lacks sufficient corrosion resistance in some environments. For example, in humid environments, brass plating is prone to selective corrosion, forming penetrating cracks and inducing pitting corrosion in the steel wire matrix. In corrosive media such as salt ions, oxidation reactions easily occur, generating loose corrosion products that accelerate plating peeling, ultimately leading to a significant decrease in adhesion to rubber.
[0003] To improve the corrosion resistance of steel cords while ensuring good interfacial adhesion with the rubber matrix, surface coating treatment has become a core process. Developing a steel cord coating treatment technology that combines high corrosion resistance, strong interfacial adhesion, and compliance with green manufacturing requirements is of great significance for improving the reliability of rubber composite materials and reducing the total life cycle cost. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of traditional steel wire cord brass plating, which has insufficient corrosion resistance and is prone to peeling in humid environments, by providing a high corrosion-resistant steel wire cord and its preparation process that strengthens the corrosion resistance of the steel wire substrate and the plating itself.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a process for preparing a high corrosion-resistant steel wire cord, comprising: The surface of the steel wire is subjected to phosphate treatment to obtain a steel wire to be plated with an inorganic phosphate coating on the surface; the inorganic phosphate is filled with silicon dioxide nanoparticles. To coat steel wire with a metal layer, the steel wire coating is obtained. The coated steel wire is then drawn and twisted to form steel wire cord. The coating of the steel wire cord is post-treated to obtain steel wire cord with post-treated surface.
[0006] Furthermore, the inorganic phosphide accounts for 0.02 to 0.1% of the total mass of the coating.
[0007] In one embodiment, the phosphate treatment of the steel wire surface includes: The steel wire is first passed through a substance containing F. - The steel wire is activated by an activating solution, and then immersed in the first phosphating solution for phosphating treatment.
[0008] Furthermore, the F in the activation solution - The content is 0.1~0.3g / L, and the pH is 1.5~2.0.
[0009] Furthermore, the first phosphating solution contains phosphate and zinc ions, with the phosphate content being 35~45 g / L and the mass ratio of phosphate to zinc ions being 3.75~13.33. The first phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%.
[0010] Furthermore, the activation time of the steel wire in the activation solution is 3~8 seconds.
[0011] In another embodiment, the phosphating treatment of the steel wire surface includes: The steel wire was directly immersed in a solution containing F. - Phosphating is carried out in the second phosphating solution.
[0012] Furthermore, the second phosphating solution contains F - Phosphate and zinc ions, F - The content of zinc ions is 0.05~0.20 g / L, the content of phosphate ions is 35~45 g / L, the mass ratio of phosphate ions to zinc ions is 3.75~13.33, the second phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%, and the pH of the second phosphating solution is 2.0~3.0.
[0013] Furthermore, the immersion time t of the steel wire in the first phosphating solution or the second phosphating solution satisfies the condition L / t = 0.15~0.24 m / s with respect to the ineffective immersion length L.
[0014] Further, the metal layer to be plated on the steel wire includes: A copper-nickel metal layer is plated onto the steel wire to be plated, and the nickel and copper contents satisfy b / a = 11.4~20.0, where a and b are the masses of nickel and copper, respectively; or, A copper-nickel-zinc metal layer is plated onto the steel wire to be plated, and the contents of copper and zinc satisfy b / c=1.425~1.714, the contents of nickel and zinc satisfy a / c=0.075~0.143, and the contents of copper, nickel, and zinc satisfy b / (a+c)=1.267~1.579, where a, b, and c are the masses of nickel, copper, and zinc, respectively.
[0015] Furthermore, the nickel is distributed in an M-order pattern throughout the coating.
[0016] Furthermore, the post-treatment of the steel wire cord coating includes: The steel cord coating is immersed in a highly dispersed post-treatment solution for post-treatment to obtain a surface-treated steel cord.
[0017] Further, the post-treatment solution comprises the following components in parts by mass: 100 parts of pure water, 0.03 to 0.05 parts of 10-25 μm spherical zinc particles, and 2 to 5 parts of potassium salt of high-carbon phosphate and potassium salt of isomeric alcohol phosphate, wherein the mass ratio of potassium salt of high-carbon phosphate to potassium salt of isomeric alcohol phosphate is ≤1.
[0018] Furthermore, the temperature of the post-treatment solution is 70~80℃, and the immersion time is 5~10s.
[0019] In a second aspect, the present invention provides a high corrosion-resistant steel wire cord, which is prepared according to the preparation process of the high corrosion-resistant steel wire cord described in any one of the first aspects.
[0020] Compared with the prior art, the present invention has the following beneficial effects: Compared to traditional steel wire cords, the cord of this invention enhances the corrosion resistance of the steel wire substrate and the coating itself. Through the synergistic effect of the three phases from the inside out—the surface of the steel wire substrate, the coating, and the surface treatment of the coating—the cord itself is protected, which greatly enhances the resistance of the steel wire cord to environmental corrosive media, especially to humid and hot corrosive media, and does not deteriorate its bonding ability with rubber. Attached Figure Description
[0021] Figure 1 This is a diagram showing the distribution of nickel in the coating in Example 1 of the present invention; Figure 2 This is a comparison of the surface color of the 7×7 structure steel wire cord DH in Embodiment 1 of the present invention and the existing brass-plated 7×7 structure steel wire cord D. Figure 3 This is a comparison image of the 7×7 structure steel wire cord DH in Embodiment 1 of the present invention and the existing 7×7 structure steel wire cord D with brass plating after 8 hours of wet heat corrosion. Figure 4 This is a comparison image of the 7×7 structure steel wire cord DH in Embodiment 1 of the present invention and the existing 7×7 structure steel wire cord D with brass plating after 24 hours of wet heat corrosion. Figure 5 This is a comparison chart showing the weight gain after salt spray corrosion of the 7×7 structure steel wire cord DH in Embodiment 1 of the present invention and the existing 7×7 structure steel wire cord D with brass plating. Figure 6This is a comparison of the surfaces of the 7×7 structure steel wire cord DH in Embodiment 1 of the present invention and the existing 7×7 structure steel wire cord D with brass plating after salt spray corrosion. Detailed Implementation
[0022] The present invention will be further described below with reference to specific embodiments. These embodiments are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0023] This invention provides a process for preparing high corrosion-resistant steel wire cord, comprising: Step 1: Phosphate the surface of the steel wire to obtain a steel wire to be plated with inorganic phosphates on the surface. Step 2: Coat the steel wire with a metal layer to obtain the steel wire coating. Then, draw and twist the coated steel wire to form a steel wire cord. Step 3: Perform post-treatment on the steel wire cord coating to obtain surface-treated steel wire cord.
[0024] Among them, the inorganic phosphide and the entire coating satisfy P / W=0.02~0.1%, where P is the mass of the inorganic phosphide and W is the total mass of the entire coating.
[0025] In one embodiment, step 1, phosphate treatment of the steel wire surface, includes: The steel wire is first passed through a substance containing F. - The steel wire is activated by an activating solution, and then immersed in the first phosphating solution for phosphating treatment.
[0026] Wherein, F in the activation solution - The content is 0.1~0.3g / L, and the pH is 1.5~2.0.
[0027] In the activation solution, F - Sources include metallic inorganic substances such as potassium fluoride, sodium fluoride, or zinc fluoride.
[0028] The steel wire is activated in an activating solution containing F- for 3 to 8 seconds.
[0029] The first phosphating solution contains phosphate and zinc ions, with the phosphate content being 35~45 g / L and the mass ratio of phosphate to zinc ions being 3.75~13.33. The first phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%.
[0030] In another embodiment, the phosphating treatment of the steel wire surface in step 1 includes: The steel wire was directly immersed in a solution containing F. - Phosphating is carried out in the second phosphating solution.
[0031] The second phosphating solution contains F - Phosphate and zinc ions, F - The content of zinc ions is 0.05~0.20 g / L, the content of phosphate ions is 35~45 g / L, the mass ratio of phosphate ions to zinc ions is 3.75~13.33, the second phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%, and the pH of the second phosphating solution is 2.0~3.0.
[0032] In the second phosphating solution, F - Sources include metallic inorganic substances such as potassium fluoride, sodium fluoride, or zinc fluoride.
[0033] In the two embodiments described above, the immersion time t of the steel wire in the first phosphating solution or the second phosphating solution satisfies the condition L / t = 0.15~0.24 m / s.
[0034] The coating contains nickel, but nickel is not present alone in the coating, and the coating also contains copper or zinc. When the coating contains only nickel and copper, the ratio of nickel to copper satisfies a / b = 11.4~20.0, where a and b are the masses of nickel and copper, respectively. When the coating contains nickel, copper, and zinc, the ratio of nickel to zinc satisfies a / c = 1.425~1.714, the ratio of copper to zinc satisfies b / c = 0.075~0.143, and the ratio of nickel to copper and zinc satisfies a / (b+c) = 1.267~1.579, where a, b, and c are the masses of nickel, copper, and zinc, respectively. The coating does not contain nickel or zinc alone.
[0035] The nickel is distributed in an M-order pattern throughout the coating.
[0036] In step 2, the process of coating the steel wire with a metal layer includes: A copper-nickel metal layer is plated onto the steel wire to be plated, and the nickel and copper contents satisfy b / a = 11.4~20.0, where a and b are the masses of nickel and copper, respectively; or, A copper-nickel-zinc metal layer is plated onto the steel wire to be plated, and the contents of copper and zinc satisfy b / c=1.425~1.714, the contents of nickel and zinc satisfy a / c=0.075~0.143, and the contents of copper, nickel, and zinc satisfy b / (a+c)=1.267~1.579, where a, b, and c are the masses of nickel, copper, and zinc, respectively.
[0037] Step 3, the post-treatment of the steel wire cord coating, includes: The steel cord coating is immersed in a highly dispersed post-treatment solution for post-treatment to obtain a surface-treated steel cord.
[0038] The post-treatment solution comprises the following components in parts by mass: 100 parts of pure water, 0.03 to 0.05 parts of 10-25 μm spherical zinc particles, and 2 to 5 parts of potassium salt of high-carbon phosphate and potassium salt of isomeric alcohol phosphate, wherein the mass ratio of potassium salt of high-carbon phosphate to potassium salt of isomeric alcohol phosphate is ≤1.
[0039] Among them, high-carbon phosphate potassium salts can be octyl phosphate potassium salts, dodecyl phosphate potassium salts, octadecyl phosphate potassium salts, etc., while isomeric alcohol phosphate potassium salts mainly include C8-C 10 Potassium phosphate salts, such as isodecyl phosphate potassium salt and isononyl phosphate potassium salt.
[0040] In step 3, the temperature of the post-treatment solution is 70~80℃, and the immersion time of the steel wire cord coating in the post-treatment solution is 5~10s.
[0041] The present invention also provides a high corrosion-resistant steel wire cord, which is prepared according to the aforementioned preparation process.
[0042] Before or during the application of inorganic phosphide, the surface of the steel wire substrate in this invention is activated with an acidic solution containing fluoride ions. This activates the steel wire substrate with the ability to remove residual oxides and also provides a certain degree of micro-etching, creating anchor points for the adhesion of the inorganic phosphide. Simultaneously, the steel wire undergoes phosphating treatment with an inorganic solution containing silica nanoparticles, resulting in the formation of inorganic phosphide on the surface of the steel wire substrate with pores filled by silica nanoparticles. This inorganic phosphide not only provides ample protection for the steel wire substrate but also exhibits excellent permeability, allowing the surface coating to penetrate and adhere more strongly to the steel wire substrate, thus better protecting it. The post-treatment solution uses potassium phosphate salts due to their excellent rust-preventive properties on metal surfaces and their compatibility with rubber. Among them, isomeric alcohol phosphate potassium salts have low dynamic surface tension due to their water solubility, and the resulting isomeric alcohol phosphate anions have excellent permeability, forming a negatively charged layer with zinc adsorption, thus enhancing electrostatic repulsion between particles. High-carbon phosphate potassium salts are water-soluble, giving the solution excellent high-temperature stability, and also enhancing the dispersion of particulate zinc. Through mechanical and physical methods, the post-treatment solution achieves more uniform dispersion. Simultaneously, the particulate zinc and potassium phosphate salts work synergistically to protect the steel cord surface, further enhancing the cord's corrosion resistance. The nickel in the coating works synergistically with the post-treatment solution to improve the coating's corrosion resistance. This invention, through the synergistic effect of the steel wire substrate surface, the coating, and the coating surface treatment, provides comprehensive protection for the cord from the inside out, significantly enhancing the steel wire coating's resistance to environmental corrosive media, especially humid and hot corrosive media.
[0043] The following section uses a 7×7 structure cord of the preferred embodiment as an example to describe in detail the entire implementation process and results of the present invention, and compares its relevant performance with that of existing brass-plated cords of the same structure.
[0044] Example 1
[0045] Before obtaining the coating, a 1.52mm surface-cleaned steel wire was first immersed in an activation solution containing 0.2g / L sodium fluoride at pH 1.8 for 5 seconds. Then, it was immersed in a first phosphating treatment solution containing phosphate, zinc ions, and 0.03% silica nanoparticles. The phosphate to zinc ion ratio was 8.5, the phosphate content was 35g / L, and the treatment speed was 0.2m / s. This yielded a steel wire containing inorganic phosphate. The wire was then plated with copper, nickel, and zinc, respectively, followed by diffusion to form an alloy coating. The nickel distribution in the coating exhibited an M-order pattern. Figure 1 The figure shows the nickel distribution after linear scanning of the entire coating. The ratio of copper to zinc in the coating is 1.573, the ratio of nickel to zinc is 0.093, and the ratio of copper to nickel-zinc is 1.439. The inorganic phosphate on the surface of the steel wire accounts for 0.06% of the total mass of the coating. After wet drawing and twisting, a 7×7 structure steel wire cord was obtained from a 1.52 mm steel wire with the coating. The steel wire cord was effectively immersed for 8 seconds in a highly dispersed post-treatment solution, which contained 100 parts of pure water, 0.04 parts of 10-25 μm spherical zinc particles, and a total of 3 parts of potassium dodecyl phosphate and potassium isodecyl phosphate, with 1 part of potassium dodecyl phosphate and 2 parts of potassium isodecyl phosphate. The solution temperature was 75 °C, resulting in a surface-treated steel wire cord.
[0046] The 7×7 structure steel wire cord of this invention is named DH, while the existing 7×7 structure steel wire cord with brass plating is named D. A comparison of the surface colors of cords D and DH is shown in the figure below. Figure 2 As shown, the two have slight color differences. The surface color of the cord DH of the present invention is more yellowish-white, while the existing brass-plated cord D is golden yellow.
[0047] Example 2
[0048] Cut equal lengths of both D and DH cords and place them in a humidity chamber for 8 hours and 24 hours, respectively. The conditions of the humidity chamber were 70℃ and 95% relative humidity. After removal, the surface corrosion of the two cords was compared. Figure 3 and Figure 4 As shown, after 8 hours of damp heat corrosion, the surface coating of the traditional brass cord D has turned gray and dark. After 24 hours of corrosion, almost the entire surface of cord D has been corroded and turned blackish-gray. As the corrosion time increases, the degree of corrosion of the cord intensifies. Compared with the cord DH of the present invention, the surface state is significantly different. The cord of the present invention shows little difference in surface color change whether it is corroded for 8 hours or 24 hours, indicating that the damp heat resistance of the cord of the present invention is significantly better than that of the traditional brass cord D.
[0049] Example 3
[0050] After weighing 1 m lengths of D and DH cords respectively, they were placed simultaneously in a salt spray chamber. The salt spray consisted of a 5% NaCl solution, the temperature was 35℃, the humidity was 85%-98%, and the salt spray settling velocity was 1-2 mL / h·80 cm. 2 The salt spray corrosion was carried out for 1 hour. The salt spray-corroded cords were then removed, dried, and weighed. The weight gain of the two cords was compared, as were the surface morphologies after corrosion. The weight gain results of the two cords after salt spray corrosion are shown below. Figure 5 As shown. From Figure 5 As shown in the bar chart, the weight gain per meter of cord D and DH before and after salt spray corrosion was 0.1365 g and 0.0363 g, respectively. The difference in weight gain between the two cords after corrosion is significant. The weight gain of the cord DH of this invention is significantly lower than that of the traditional cord D, indicating that the cord DH of this invention has better salt corrosion resistance. Furthermore, the degree of corrosion can be clearly distinguished from the visual comparison images of the two cords after corrosion. Figure 6 As shown, corresponding to the weight gain of the cord after corrosion, the cord DH of the present invention has a brighter color after corrosion, while the traditional brass cord D has a noticeably darker surface with rust spots after corrosion.
[0051] Example 4
[0052] The adhesion properties of the cord DH of this invention and the traditional brass cord D to rubber were compared, and the results are shown in Table 1. The cords DH and D of this invention were vulcanized with rubber, respectively. Initial adhesion force was the force required to pull the cord out of the rubber after vulcanization at a certain temperature and time. 10% saline aging involved immersing the vulcanized cord and rubber in a 10% NaCl solution for 7 days before cord extraction. 93℃ / 95%RH damp heat aging involved placing the vulcanized cord and rubber in a chamber at 93℃ and 95% relative humidity for 7 days before cord extraction. 100℃ hot air aging involved placing the rubber and cord vulcanized block in a constant-temperature blower at 100℃ for 7 days. The cord extraction force and adhesive adhesion rate reflected the strength of the bond between the cord and rubber.
[0053] Table 1 Comparison of the adhesive properties of cords D and DH with rubber
[0054] As shown in Table 1, the initial adhesion between the cord DH of this invention and rubber is comparable to that of the traditional brass cord D, indicating that the cord DH of this invention does not adversely affect its bonding with rubber. To verify the adhesion between the cord DH of this invention and rubber under harsh conditions, salt water, hot air, and humid heat immersion tests were conducted, and compared with the traditional cord D. Table 1 shows that after 7 days of salt water and humid heat aging, the adhesion between cord D and rubber is slightly lower than that of cord DH of this invention, especially in terms of humid heat aging adhesion. The adhesive rates of both are basically the same. After 7 days of hot air aging, the adhesion between both and rubber is basically the same, with no significant difference.
[0055] In summary, compared with traditional steel wire cords, the cord of the present invention significantly enhances the corrosion resistance of the steel wire substrate and the coating itself, greatly strengthening the protective effect of the coating on the substrate without deteriorating its bonding ability with rubber. It also delays the peeling phenomenon at the interface between the cord and the rubber caused by the corrosion of the steel wire itself, extends the service life of rubber-reinforced products, and improves product safety.
[0056] Those skilled in the art should note that the embodiments of the present invention described in detail are only one preferred implementation method and are not intended to limit the technology. Modifications or equivalent substitutions to the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and should all be covered within the scope of protection.
Claims
1. A manufacturing process for a high corrosion-resistant steel wire cord, characterized in that, include: The surface of the steel wire is phosphated to obtain a steel wire to be plated with inorganic phosphates on the surface. The inorganic phosphide is filled with silica nanoparticles; To coat steel wire with a metal layer, the steel wire coating is obtained. The coated steel wire is then drawn and twisted to form steel wire cord. Post-treatment is performed on the coating of the steel wire cord to obtain steel wire cord with surface post-treatment. The phosphate treatment of the steel wire surface includes: The steel wire is first passed through a substance containing F. - The wire is activated with an activating solution, and then immersed in the first phosphating solution for phosphating treatment; or, The steel wire was directly immersed in a solution containing F. - Phosphating is carried out in the second phosphating solution; F in the activation solution - The concentration is 0.1~0.3 g / L, the pH is 1.5~2.0, and the activation time is 3~8 s; the first phosphating solution contains phosphate and zinc ions, the phosphate concentration is 35~45 g / L, the mass ratio of phosphate to zinc ions is 3.75~13.33, and the first phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%; The second phosphating solution contains F - Phosphate and zinc ions, F - The content of phosphate is 0.05~0.20g / L, the content of phosphate is 35~45g / L, the mass ratio of phosphate to zinc ions is 3.75~13.33, the second phosphating solution also contains a silica nanoparticle dispersion phase with a mass fraction of 0.01~0.05%, and the pH of the second phosphating solution is 2.0~3.0; The metal coating to be plated on the steel wire includes: A copper-nickel metal layer is plated onto the steel wire to be plated, and the nickel and copper contents satisfy b / a = 11.4~20.0, where a and b are the masses of nickel and copper, respectively; or, Copper, nickel, and zinc metal layers are plated onto the steel wire to be plated, and the contents of copper and zinc satisfy b / c=1.425~1.714, the contents of nickel and zinc satisfy a / c=0.075~0.143, and the contents of copper, nickel, and zinc satisfy b / (a+c)=1.267~1.579, where a, b, and c are the masses of nickel, copper, and zinc, respectively. The post-treatment of the steel wire cord coating includes: The steel wire cord coating is immersed in a highly dispersed post-treatment solution for post-treatment to obtain a surface-post-treated steel wire cord. The post-treatment solution comprises the following components in parts by mass: 100 parts of pure water, 0.03 to 0.05 parts of 10-25 μm spherical zinc particles, and 2 to 5 parts of potassium salt of high-carbon phosphate and potassium salt of isomeric alcohol phosphate, wherein the mass ratio of potassium salt of high-carbon phosphate to potassium salt of isomeric alcohol phosphate is ≤1.
2. The preparation process of the high corrosion-resistant steel wire cord according to claim 1, characterized in that, The inorganic phosphide accounts for 0.02 to 0.1% of the total mass of the coating.
3. The preparation process of the high corrosion-resistant steel wire cord according to claim 1, characterized in that, The immersion time t of the steel wire in the first or second phosphating solution and the effective immersion length L satisfy L / t = 0.15~0.24 m / s.
4. The preparation process of the high corrosion-resistant steel wire cord according to claim 1, characterized in that, Nickel is distributed in an M-order pattern throughout the coating.
5. The preparation process of the high corrosion-resistant steel wire cord according to claim 1, characterized in that, The temperature of the post-treatment solution is 70~80℃, and the immersion time is 5~10s.
6. A high corrosion-resistant steel wire cord, characterized in that, The high corrosion-resistant steel wire cord is prepared according to the preparation process of any one of claims 1 to 5.
Citation Information
Patent Citations
Method for manufacturing highly corrosion-resistant steel wire rope for fishery
CN104928956A
One-step electroplating brass steel wire post-plating treatment method
CN111979568A